Coordination polymer glass from a protic ionic liquid: proton conductivity and mechanical properties as an electrolyte. Issue 20 (12th May 2020) - Ogawa, Tomohiro; Takahashi, Kazuki; Nagarkar, Sanjog S.; Ohara, Koji; Hong, You-lee; Nishiyama, Yusuke; Horike, Satoshi
Abstract : A proton-conducting coordination polymer glass derived from a protic ionic liquid works as a moldable solid electrolyte and the anhydrous fuel cell showed I – V performance of 0.15 W cm −2 at 120 °C. Abstract : High proton conducting electrolytes with mechanical moldability are a key material for energy devices. We propose an approach for creating a coordination polymer (CP) glass from a protic ionic liquid for a solid-state anhydrous proton conductor. A protic ionic liquid (dema)(H2 PO4 ), with components which also act as bridging ligands, was applied to construct a CP glass (dema)0.35 [Zn(H2 PO4 )2.35 (H3 PO4 )0.65 ]. The structural analysis revealed that large Zn–H2 PO4 − /H3 PO4 coordination networks formed in the CP glass. The network formation results in enhancement of the properties of proton conductivity and viscoelasticity. High anhydrous proton conductivity ( σ = 13.3 mS cm −1 at 120 °C) and a high transport number of the proton (0.94) were achieved by the coordination networks. A fuel cell with this CP glass membrane exhibits a high open-circuit voltage and power density (0.15 W cm −2 ) under dry conditions at 120 °C due to the conducting properties and mechanical properties of the CP glass.